DNA Damage in Prader Willi Syndrome Against Obesity - Diennisa Mursalin (Journal of Biodiversity and Biotechnology, 2023)
Prader Willi Syndrome is a multisystem genetic disorder caused by deletions of paternal chromosomes (75%), maternal chromosomal dysomi (25%), and translocations (1%). This syndrome has a main characteristic, namely the state of obesity in individuals sufferers where. This is due to deficiency of Growth Hormone levels due to central hypothalamic-limbic disorders that occur in this syndrome. This syndrome has a characteristic course of obesity in every phase of life. The obesity that is characteristic of this syndrome causes diverse complications because it causes DNA damage through chronic inflammation caused by an increase in pro-inflammatory cytokines due to the buildup of adipose tissue. Thus, individuals with PWS can experience various metabolic diseases that can increase their morbidity and mortality.